The Commissioner for Conciliation, Mediation and Arbitration Office in South Africa: Serving the Interest of the Powerful or the Powerless? - Mokoko Sebola (Journal of Governance Risk Management Compliance and Sustainability, 2023)
Legislatively, the Office of the Commissioner for Conciliation Mediation and Arbitration (CCMA) in the South was created to ensure a fast, convenient, and fair labour dispute mechanism within the labour force environment. While some believe that the Office is fair in the adjudication of cases brought to them, this article argues differently from such held viewpoint. This article argues that the Office of the CCMA largely serves the interest of the Powerful (Employers) and largely ignores the Powerless (Employees). There are few if any, scholarly articles which addressed this crucial element of injustice against the working class in South Africa, which emanates from the ineffective operation of this institution. This article is conceptual in approach, and it uses literature to argue that the current ineffective systems used in the CCMA office ensure little security and protection of employees' rights against well-resourced and labour-abusive employers. The article concludes that the unfair balance of consideration of the interests of the employers and employees at the CCMA renders the purpose of the office ineffective, with no valid moral reason to exist in South Africa.